Search for CP violation through an amplitude analysis of D0 → K+K−π+π− decays; Journal of High Energy Physics; Vol. 2019, iss. 2 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Adeva B. Bernardo; Shapkin M. M. Mikhail Mikhaylovich; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich (2019, 2019)
Title screen